2002
DOI: 10.1128/iai.70.3.1272-1278.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingival CD14+Fibroblasts Primed with Gamma Interferon Increase Production of Interleukin-8 in Response to Lipopolysaccharide through Up-Regulation of Membrane CD14 and MyD88 mRNA Expression

Abstract: Gamma interferon (IFN-γ)-primed human gingival fibroblasts (HGF) have been shown to produce higher levels of interleukin-8 (IL-8) upon stimulation with bacterial products and inflammatory cytokines than nonprimed controls. In this study, we examined whether priming of HGF with IFN-γ up-regulates IL-8 production by the cells in response to purified lipopolysaccharide (LPS). The priming effect of IFN-γ was clearly observed in the high-CD14-expressing (CD14high) HGF but not in the low-CD14-expressing (CD14low) HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 44 publications
2
44
1
2
Order By: Relevance
“…Alternatively, the priming activity of IFN-ª may be due to augmentation of the TLR-MyD88 signalling pathway, which mediates signalling not only of gram-negative but also of gram-positive bacterial cell-surface components, irrespective of CD14 [44][45][46]. In this context, this group confirmed that IFN-ª up-regulated mCD14 expression and MyD88 mRNA expression by human gingival fibroblasts, and resulted in enhanced production of IL-8 by the cells in response to Salmonella LPS [29]. Faure et al reported that IFN-ª induced TLR2 and TLR4 expression in human endothelial cells.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Alternatively, the priming activity of IFN-ª may be due to augmentation of the TLR-MyD88 signalling pathway, which mediates signalling not only of gram-negative but also of gram-positive bacterial cell-surface components, irrespective of CD14 [44][45][46]. In this context, this group confirmed that IFN-ª up-regulated mCD14 expression and MyD88 mRNA expression by human gingival fibroblasts, and resulted in enhanced production of IL-8 by the cells in response to Salmonella LPS [29]. Faure et al reported that IFN-ª induced TLR2 and TLR4 expression in human endothelial cells.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies [26][27][28] showed that human gamma-interferon (IFN-ª) primed human gingival fibroblasts (HGF) to enhance production of inflammatory cytokines upon stimulation with the LPS fraction from black-pigmented bacteria (BPB) such as Porphyromonas gingivalis and Prevotella intermedia. Furthermore, IFN-ª primed HGF which highly expressed membrane CD14 (mCD14) to increase expression of mCD14 and mRNA for CD14, TLR4 and MyD88, resulting in production of higher levels of IL-8 than non-primed cells upon stimulation with purified Salmonella LPS [29].…”
Section: Introductionmentioning
confidence: 99%
“…These observations also suggest that HGF in inflamed regions are actively involved in the inflammatory process by producing high concentrations of chemokines in response to exogenous IL-2/IL-15 as well as LPS. It has previously been shown that normal HGF primed with IFN-␥ produce increased levels of chemokines in response to LPS through up-regulation of CD14 and MyD88 mRNA expression (5). IFN-␥ treatment (1000 IU/ml for 3 days) induced the expression of IL-15R␣ mRNA, but had no effect on the expression of IL-2R␣ mRNA and surface expression of IL-15 (Ref.…”
Section: Discussionmentioning
confidence: 97%
“…Fibroblasts are not a homogeneous population in different anatomical regions or even within a single tissue, and are considered to actively define the structure of microenvironments and modulate immune cell behavior by conditioning the local and cellular microenvironment (1,2). Human gingival fibroblasts (HGF), 3 the major constituent of gingival connective tissue, have been shown to express immunologic receptors, such as a bacterial pattern recognition receptor CD14 (3,4), TLRs (5), and costimulatory molecule CD40 (1,6) and to produce various cytokines, such as IL-1, IL-6, IL-8, and MCP-1, by interaction with their ligands (3)(4)(5)7). These observations indicate that HGF also actively participate in immune responses and inflammatory processes.…”
mentioning
confidence: 99%
“…[19][20][21][22] Those priming effects were mediated by an upregulation of TLR4 and/or other downstream signaling molecules including MD2, CD14, and MyD88. [20][21][22][23] These results are intriguing with regard to hepatic injury and inflammation because many proinflammatory cytokines, such as TNF-a, are upregulated in patients with liver cirrhosis and liver injury. 24,25 Therefore, we hypothesized that the inflammatory reaction induced by the gram-positive bacterial cell wall components is also enhanced in an injured liver.…”
mentioning
confidence: 99%